2020
DOI: 10.1007/s00068-020-01412-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcome of rib fractures: a nationwide study in the Netherlands

Abstract: Purpose Rib fractures following thoracic trauma are frequently encountered injuries and associated with a significant morbidity and mortality. The aim of this study was to provide current data on the epidemiology, in-hospital outcomes and 30-day mortality of rib fractures, and to evaluate these results for different subgroups. Methods A nationwide retrospective cohort study was performed with the use of the Dutch Trauma Registry which covers 99% of the acutely admitted Dutch trauma population. All patients age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 19 publications
5
31
0
2
Order By: Relevance
“…The incidence rate increased sharply with age, from 34 to 107 per 100,000 person years in patients aged ≤ 65 years and ≥ 65 years, respectively. The incidence rate of 72 per 100,000 person years for admitted elderly patients is again in line with previous literature [18,20]. Furthermore, the increase of 37% of the total number of patients with rib fractures between 2015 and 2018 demonstrates that rib fractures are a common and increasing problem, especially among the elderly [33].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The incidence rate increased sharply with age, from 34 to 107 per 100,000 person years in patients aged ≤ 65 years and ≥ 65 years, respectively. The incidence rate of 72 per 100,000 person years for admitted elderly patients is again in line with previous literature [18,20]. Furthermore, the increase of 37% of the total number of patients with rib fractures between 2015 and 2018 demonstrates that rib fractures are a common and increasing problem, especially among the elderly [33].…”
Section: Discussionsupporting
confidence: 89%
“…The incidence rate of 29 per 100,000 person years for admitted patients is similar to the incidence rate demonstrated by a recent study focusing only on admitted patients [18]. The incidence rate for the total cohort of 47 per 100,000 person years showed that rib fractures are common and not all patients require admission.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The aim of the DTR is to uphold and monitor good standard of care for injured patients. The DTR has been used for nationwide retrospective cohort studies before, such as Peek et al 15 . The DTR contains data of all trauma patients who were admitted to hospital through A&E, within 48 h of trauma.…”
Section: Methodsmentioning
confidence: 99%
“…This was probably underestimated herein as those suffering minor thoracic injuries (AIS Thorax =1), including single rib fractures, were excluded. Peek et al recently reported in their nationwide studies that single rib fracture were frequently encountered injuries (20% of rib fractures) [24,25]. We chose not to include these patients because previous studies have demonstrated that these single rib fractures were not associated with mortality [9].…”
Section: Discussionmentioning
confidence: 99%